The impact of the media and social networks on the mental health of the population. review study - Sánchez-Carlessi, Héctor Hugo (2024)
Literature review study aimed at identifying empirical research that allows us to know to what extent the frequent use of digital media and especially social networks can affect the mental health of the population. To carry out the study, information was collected from scientific articles from publications published in Peru and abroad, from those magazines that are registered in high-impact databases such as Scielo, Scopus and WoS. Publications made before the pandemic, those published during the COVID-19 pandemic and those published post-pandemic were considered. In all cases, it was found that the frequent use of the Internet and especially social networks such as Instagram, WhatsApp, Face Book and Twitter (X) have disrupted the mental health, especially of children and young people, especially those born in the middle of the century. XXI where the use of social networks expanded due to the appearance of smartphones. These changes have mainly influenced an increase in levels of anxiety, depression, stress, and sleep disorders, among the most important. This impact is so serious that some countries have begun to restrict or prohibit the use of smart cell phones by children under 16 years of age.